Analysis of Tennis Competitions on Different Court Surfaces - İhsan Doğan; Şükran Arıkan; Serkan Revan (Selcuk University, 2021)
The purpose of this study is to analyze the match statistics of men and women tennis players in the singles category in the 2019 Grand Slam tennis tournaments (Australian Open, French Open, Wimbledon, US Open) according to different court surfaces. Winning matches in 1004 competitions made up of 250 men's singles and 252 women's singles played on hard court (US Open and Australian Open); 127 men's singles and 122 women's singles played on the clay court (French Open); and 127 men's singles and 126 women's singles played on grass court (Wimbledon) were analyzed. SPSS 22.0 statistical package program was used to evaluate the data and find the calculated values. As the data showed normal distribution, One-Way Analysis of Variance (ANOVA) was used for comparisons of more than two sets. Tukey HSD multiple comparison test was used to determine the source of significant differences as a result of ANOVA. The level of significance in the study was taken as 0.05. It was determined that ace in women athletes, winning % on 1st serve, unforced error and the fastest service variables differ significantly based on the court grounds (p lt;0.05). In male athletes, it was determined that ace, double fault, winning % on 1st serve, break points won, unforced errors, fastest service and match duration variables differ significantly according to court surfaces (p lt;0.05). As a result, the findings show that the game elements that affect the outcome of the match are affected by the court surface and players tend to change their game patterns, in other words, the tactical structure of the important game elements that will make the match win and to adapt themselves to the playing court surface.